Determining the Multi-Modal Interactive Nature of Foot Reflexology for Virtual Reality Stress Therapy Application - OKERE , PRINCE-HECTOR CHIMEREMEZE (2014)
The application ofmulti-modal interactivity in virtual reality (VR) avails ahost of advantages which includes enhancement of realism and the achievement of interactivity that is relatively close or identical to the conventional human interactions. Haptics, visual and aural interactions have been widely applied in various domains for numerous purposes, ranging from the medical industry to engineering/auto mobile industry. The proliferation of virtual reality stress therapy applications particularly in the attempt towards the virtualization of foot reflexology therapy through the four key components for design which includes the virtual world, immersion, sensory feedback and interactivity. However, very little is understood on the haptic, visual and aural interactive nature, corresponding to user activities in the therapy and to what extent they contribute in relaxation and stress relief.